Secondary metabolites from Sterculia lychnophora Hance (Pangdahai). (October 2020) - Oppong, Mahmood Brobbey; Zhang, Bing-Yang; Fang, Shi-Ming; Qiu, Feng
Abstract: From the ethanolic extracts of dried seeds of Sterculia lychnophora Hance Pierre (Malvaceae), a total of twenty-two (22) compounds were isolated. These included one lignan (1), three phenylpropanoids (5 –6, 21), two flavonoid glycosides (8 –9), two sesquiterpenoids ( 3, 17), two nucleosides (10, 12), three nitrogenous bases (4, 7, 14), three phenolic acids (2, 13, 20), two heterocyclic aromatic acids (11, 16) and two phytosteroids (18 –19). For eighteen out of the 22 compounds, there is no report of their presence in S. lychnophora . There is no report of sixteen of them being present in the Sterculia genus, hence the first report. The isolated compounds showed a significant taxonomic relationship between S. lychnophora and other species of genus Sterculia. Compounds 13 and 20 might serve as important taxonomic markers for the Sterculia genus. Graphical abstract: Image 1 Highlights: Twenty-two compounds were from ethanolic extracts of Pangdahai. Eighteen compounds were isolated from Pangdahai for the first time. Sixteen compounds were reported from the Sterculia genus for the first time. The isolated compounds were identified as lignan, phenylpropanoids, flavonoid glycosides, sesquiterpenoids, among others. Compounds 13 and 20 might serve as important taxonomic markers for Sterculia genus.